Identification and characterization of the factor H and FHL-1 binding complement regulator-acquiring surface protein 1 of the Lyme disease spirochete Borrelia spielmanii sp. nov - Herzberger, Pia; Siegel, Corinna; Skerka, Christine; Fingerle, Volker; Schulte-Spechtel, Ulrike; Wilske, Bettina; Brade, Volker; Zipfel, Peter F.; Wallich, Reinhard; Kraiczy, Peter (International journal of medical microbiology, 2009)
Borrelia spielmanii, one of the etiological agents of Lyme disease found in Europe, evades host complement-mediated killing by recruitment of the immune regulators factor H and FHL-1 from human serum. Serum-resistant and intermediate serum-resistant isolates express up to 3 distinct complement regulator-acquiring surface proteins (CRASPs) that bind factor H and/or FHL-1. The present study describes identification and functional characterization of BsCRASP-1 as the dominant factor H and FHL-1 binding protein of B. spielmanii. BsCRASP-1 is a 27.7kDa outer surface lipoprotein, which after processing has a predicted mass of 24.9kDa. BsCRASP-1 is encoded by a single copy gene, cspA, that maps to a linear plasmid of approximately 55kb. Ligand affinity blot techniques revealed that both native and recombinant BsCRASP-1 from different isolates can strongly bind FHL-1, but only weakly factor H. Deletion mutants of recombinant BsCRASP-1 were generated and a high-affinity binding site for factor H and FHL-1 was mapped to its carboxy-terminal 10-amino-acid residue domain. Similarly, the dominant binding site of factor H and FHL-1 was localized to short consensus repeats (SCRs) 5-7. Factor H and FHL-1 maintained cofactor activity for factor I-mediated C3b inactivation when bound to full-length BsCRASP-1 but not to a deletion mutant lacking the carboxy-terminal 10-amino-acid residue domain. In conclusion, BsCRASP-1 binds the host immune regulators factor H and FHL-1, and is suggested to represent a key molecule of B. spielmanii for complement resistance. Thus, BsCRASP-1 most likely contributes to persistence of B. spielmanii and to pathogenesis of Lyme disease.
Gesehen am 04.06.2021